Effects of Midazolam on the Development of Adult Leydig Cells From Stem Cells In Vitro - Zhao, Xingyi; Ji, Minpeng; Wen, Xin; Chen, Dan; Huang, Fu; Guan, Xiaoju; Tian, Jing; Xie, Jiajia; Shao, Jingjing; Wang, Jiexia; Huang, Luoqi; Lin, Han; et al. (Frontiers in Endocrinology, 2021)
Background: Midazolam is a neurological drug with diverse functions, including sedation, hypnosis, decreased anxiety, anterograde amnesia, brain-mediated muscle relaxation and anticonvulsant activity. Since it is frequently used in children and adolescents for extended periods of time, there is a risk that it may affect their pubertal development. Here, we report a potential effect of the drug on the development of Leydig cells (LCs), the testosterone (T)-producing cells in the testis. Methods: Stem LCs (SLCs), isolated from adult rat testes by a magnet activated cell sorting technique were induced to differentiate into LCs in vitro for 3 weeks. Midazolam (0.1-30 μM) was added to the culture medium and the effects on LC development were assayed. Results: Midazolam has dose-dependent effects on SLC differentiation. At low concentrations (0.1-5μM), the drug can mildly increase SLC differentiation (increased T production), while at higher concentrations (15-30μM) it inhibits LC development (decreased T production). T increases at lower levels may be due to up-regulations of scavenger receptor class b Member 1 (SCARB1) and cytochrome P450 17A1 (CYP17A1), while T reductions at higher levels of Midazolam could be due to changes in multiple steroidogenic proteins. The uneven changes in steroidogenic pathway proteins, especially reductions in CYP17A1 at high Midazolam levels, also result in an accumulation of progesterone. In addition to changes in T, increases in progesterone could have additional impacts on male reproduction. The loss in steroidogenic proteins at high Midazolam levels may be mediated in part by the inactivation of protein kinase B/cAMP response element-binding protein (AKT/CREB) signaling pathway. Conclusion: Midazolam has the potential to affect ALC development at concentrations comparable to the blood serum levels in human patients. Further studies are needed to test the effects on human cells.